Cellulitis With Ulcer on Diabetes Mellitus : A Case Report - Yeppy Arief Nurzaman; Patrico Rillah Setiawan; Maxzillion Sky Kasnadi; Stefanie Sumartono; Apriani Lam; Syifa Navisah; Nadya Ariella (Rumah Sakit Unggul Karsa Medika, 2023)
Cellulitis is deep dermal and subcutaneous tissue infections. Cellulitis typically manifests as a warm, erythematous area that is poorly defined, edematous, and tender to palpation. Cellulitis may act as a trigger for the diagnosis of diabetes mellitus, and occult diabetes may be a significant actor in the development of cellulitis.